Morphological Innovations and Vast Extensions of Mountain Habitats Triggered Rapid Diversification Within the Species-Rich Irano-Turanian Genus Acantholimon (Plumbaginaceae) - Moharrek, Farideh; Sanmartín, Isabel; Kazempour-Osaloo, Shahrokh; Nieto Feliner, Gonzalo (Frontiers in Genetics, 2019)
The Irano-Turanian floristic region spans a topographically complex and climatically continental territory, which has served as a source of xerophytic taxa for neighboring regions and is represented by a high percent of endemics. Yet, a comprehensive picture of the abiotic and biotic factors that have driven diversification within this biota remains to be established due to the scarcity of phylogenetic studies. Acantholimon is an important component of the subalpine steppe flora of the Irano-Turanian region, containing c. 200 cushion-forming sub-shrubby pungent-leaved species. Our recent molecular phylogenetic study has led to enlarging the circumscription of this genus to include eight mono- or oligospecific genera lacking the characteristic life-form and leaves. Using the same molecular phylogeny, here we investigate the tempo and mode of diversification as well as the biogeographic patterns in this genus, to test the hypothesis that a combination of key morphological innovations and abiotic factors is behind Acantholimon high species diversity. Molecular dating analysis indicates that Acantholimon s.l. started to diversify between the Late Miocene and the Pliocene and the biogeographic analysis points to an Eastern Iran–Afghanistan origin. Macroevolutionary models support the hypothesis that the high diversity of the genus is explained by accelerated diversification rates in two clades associated with the appearance of morphological key innovations, such as a cushion life-form and pungent leaves; this would have favored the colonization of water-stressed, substrate-poor mountainous habitats along the newly uplifted IT mountains during the Mio-Pliocene. Given the apparent similarity of mountain habitats for most species of Acantholimon, we hypothesize that its current high species diversity responds to a scenario of non-adaptive radiation fueled by allopatric speciation rather than evolutionary radiation driven by ecological opportunity. Similar scenarios might underlie the high diversity of other speciose genera in the topographically complex Irano-Turanian landscape, though this remains to be tested with fine-grained distribution and climatic data.